THEMATIC STUDY OF "THE STORY OF MADHU" BY RUSKIN BOND - Singh, Shalini; Farooqi, Farhana (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper makes a thematic evaluation of Ruskin Bond's delicate short story, "The Story of Madhu". Through an attentive review of the text, this study tries to find out the major themes which stem out in the narrative, as childhood innocence, adolescence, human relationships, nature and environment, attraction and adorations. Conducting a thematic study of any work of art facilitates the reader gaining a deeper meaning of the text. It helps in grasping the resemblance of the text with other works of art. By tracking out the literary devices and narrative techniques practiced by Bond, this research finds out the ways in which Bond carves an impressive portrayal of childhood. The outcomes of this theme-oriented study will contribute in developing the greater understanding of complexities and significance of relations in life. This study also brings the understanding of Bond’s power of observation in his literary writing and grasp the importance of his works in Indian literature. This study considers on the socio-cultural perspectives of this story and also focuses on the significance of Bond's themes in literary and cultural debates in the present time, making it a worthy contribution to the field of literary studies.